Causese and circumstances of the appearance of the Blac Sea Cossacsks - Варга, Беата (Дриновський збірник, 2020)
The article addresses the issues to what extent the region of the Northern Black Sea Region can be considered a classic frontier; how much the Black Sea Cossack Host can be considered the successor of the Zaporizhzhya Sich and what reasons can explain the appearance of the Black Sea army. It is concluded that the steppe frontier of the Northern Black Sea Region had a number of features that contradict the example of the classic frontier, where the emergence of political power was preceded by the arrival of settlers, and the region remained within the feudal framework and eventually lost its limited autonomy. In this region, the mass migration of people to the southern territory, where there was a special system of sentry and village service, was promoted by state policy; and in new places there was practically no local settled population. The establishment of the Black Sea Cossack Host on the southern border of the Russian Empire was necessary for the state. The need to again re-organize the Cossack army from the scattered Zaporozhian Cossacks was caused primarily by the 2nd Russo-Turkish War (1787–1792) during the reign of Catherine II. However, this military formation by the Russian government was perceived as not quite a normal phenomenon, but which it tolerated because of the need to defend the southern borders and because of the military campaigns in the southern direction. The Zaporozhian Sich ceased to exist in 1775, but later revived its historical heritage in the form of the Black Sea Cossack Host. Тhe Black Sea Cossacks brought with them to their new residence - in the regions north of the Kuban River - the elements of self-government practiced in the former Zaporozhian Sich. The former Zaporozhian Cossacks transferred the traditions of Zaporizhia to new places of settlement. As a rule, these power orders limited “Cossack democracy” and put the entire Cossack structure within the framework of the Russian state system.